Exogenous vascular endothelial growth factor supplementation can restore the podocyte barrier‐forming capacity disrupted by sera of preeclamptic women. Issue 1 (28th May 2012) - Henao, Daniel E.; Cadavid, Ángela P.; Saleem, Moin A.
Abstract Aim: To determine whether exogenous vascular endothelial growth factor (VEGF) supplementation to sera from women with preeclampsia can restore the podocyte barrier‐forming capacity disrupted after stimulation with sera from these women. Material and Methods: Enzyme‐linked immunosorbent assays (ELISAs) for sFlt‐1 (soluble VEGF receptor 1) and VEGF were performed in the sera of preeclamptic and healthy pregnant women. VEGF‐enriched preeclamptic serum was used to evaluate the capacity of such sera to restore the diminished podocyte barrier capacity secondary to stimulation with untreated preeclamptic sera. Results: Two groups, preeclampsia (n = 15) and healthy (n = 15) pregnant women, were established. Median serum levels (pg/mL) of sFlt‐1 and VEGF were significantly different between groups: 3987 versus 1432 and 6 versus 15.6 (P < 0.001). Altered resistance values of podocytes stimulated with sera from women with preeclampsia were recovered after exogenous VEGF supplementation. Conclusion: The mean resistance value of cultured podocytes, an indicator of the integrity of the cytoskeleton and the capacity of these cells to form layers, is altered in women with preeclampsia. High levels of sFlt‐1, an inhibitor of VEGF observed in high concentrations in the serum of these patients, could be the underlying cause of this alteration. We provide evidence that exogenous VEGF supplementation of the sera of these women could recover this indicator.